Care dependency in older stroke patients with comorbidities: a latent profile analysis - Lin, Qinger; Dong, Xiaohang; Huang, Tianrong; Zhou, Hongzhen (Frontiers in Aging Neuroscience, 2024)
Objectives: To explore latent profiles of care dependency in older stroke patients with comorbidities and to analyze the factors influencing different latent profiles.Methods:A total of 312 older ischemic stroke patients with comorbidities were included in the analysis. Latent Profile Analysis ( LPA) was used to classify the participants into potential subgroups with different types of care dependency.The influencing factors of the classification of care dependency subgroups were determined using multivariate Logistic regression analysis.The care dependency score of older ischemic stroke patients with comorbidities was (51.35 ±13.19), and the patients could be classified into 3 profiles, namely Universal dependency (24.0%), Moderate activity-social-learning dependency (28.0%), and Mild activity-social-learning dependency (48.0%); caregiver , BI at admission, and functional impairments were independent factors influencing care dependency. (P<0.05).There are three latent profiles of care dependency in older ischemic stroke patients with comorbidities. According to the characteristics of various populations, medical staff are able to implement specific interventions to lower the level of dependency and further improve the quality of life of patients